Front Cover: Structure‐Guided Design of a Group B Streptococcus Type III Synthetic Glycan–Conjugate Vaccine (Chem. Eur. J. 31/2020). Issue 31 (11th May 2020) - Oldrini, Davide; del Bino, Linda; Arda, Ana; Carboni, Filippo; Henriques, Pedro; Angiolini, Francesca; Quintana, Jon I.; Calloni, Ilaria; Romano, Maria R.; Berti, Francesco; Jimenez‐Barbero, Jesus; Margarit, Immaculada; et al.
Abstract : Group B Streptococcus III has been considered a model of highly complex glycan epitope. Based on the X‐ray crystallographic structure of a polysaccharide fragment‐mAb complex, a hexasaccharide was synthesized comprising the positions involved in binding. After conjugation to a carrier protein and in vivo testing, the oligosaccharide was as efficacious as the natural polysaccharide in inducing protective antibodies. This study underlines the role of structural glycobiology in simplifying the design of vaccines based on complex bacterial polysaccharides. More information can be found in the Full Paper by R. Adamo et al. on page 7018 .